Research on the Source Mechanism and Source Prevention and Control System of Deep Rock Burst - Shuai Di (Advances in Civil Engineering)
Deep rock burst accidents occur frequently and become increasingly serious. Further improving the effectiveness and accuracy of the prevention and control of rock burst, ensuring the safe and efficient production of mines, clarifying the basic causes of disasters, and refining the type of deep rock burst are the most important key links. Aiming at the problems such as unclear incentives and types and the lack of effective and targeted prevention measures of deep rock burst, taking Xin’an Mine as the research background, based on the energy theory, the coal and rock mass multisource energy unified equation was established to analyze coal and rock mass instability mechanism. According to the different degrees of participation of various factors, the types of deep rock burst are determined as three categories and four types, and the corresponding judgment criteria are proposed. The precise prevention and control system for the source of rock burst with Xin’an characteristics is proposed, successfully applied to the 8101 working face, which not only guarantees the safe production of the working face, but also achieves good economic benefits. The research results lay the foundation for improving the accuracy and precision of the prevention and control of deep rock burst and provide theoretical guidance for the safe and efficient mining of the mine.